ÁREAS URBANAS DE GÉNESE ILEGAL — PROBLEMAS SUSCITADOS POR UM REGIME LEGAL EXCEPCIONAL QUE TEIMA EM PERPETUAR-SE NO TEMPO: Dulce Lopes (De Legibus - Law Journal, 2021)
The present commentary analysis the intersection between the legal frameworks of illegal urban areas and urban rehabilitation areas. It aims to clarify both the administrative and financial responsibilities in each of those regimes, taking into consideration the case decided by the Lisbon Court of Appeals.